Recent Advances in the Generation of Nitrilium Betaine 1,3-Dipoles - Livingstone, Keith; Little, Gemma; Jamieson, Craig (Synthesis, 2021)
Nitrilium betaine 1,3-dipoles are ubiquitous reagents in organic chemistry, with applications ranging from natural product synthesis to materials science. Given the high reactivity of these zwitterionic motifs, they are invariably generated in situ from a suitable precursor, prior to use. This short review summarises the recent progress in the development of modern approaches towards the formation of these 1,3-dipoles, and their applications within a diverse range of fields.1 Introduction2 Nitrile Ylides2.1 2H-Azirine Rearrangement2.2 Addition of Nitriles to Carbenes3 Nitrile Imines3.1 2,5-Tetrazole Thermolysis3.2 2,5-Tetrazole Photolysis3.3 Diaryl Sydnone Photolysis4 Nitrile Oxides4.1 Hypervalent Iodine4.2 The Nitroso Radical4.3 Green Chemistry Approaches4.4 Other Approaches5 Conclusions
Keywords: 1,3-dipole; dipolar cycloaddition; nitrilium betaine; nitrile ylide; nitrile imine; nitrile oxide; photochemistry